2010
DOI: 10.1051/0004-6361/200913387
|View full text |Cite
|
Sign up to set email alerts
|

Discrete Source Survey of 6 GHz OH emission from PNe and pPNe and first 6 GHz images of K 3–35

Abstract: Aims. The aim of this study is to investigate the physical properties of molecular envelopes of planetary nebulae (PNe) in their earliest stages of evolution. Methods. Using the 100 m telescope at Effelsberg, we have undertaken a high sensitivity discrete source survey for the first excited state of OH maser emission (J = 5/2, 2 Π 3/2 at 6 GHz) in the direction of PNe and proto-planetary nebulae (PNe) exhibiting 18 cm OH emission (main and/or satellite lines), and we further validate our detections using the N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Regarding the maser environment, Yoon et al (2014) reported no detection of 22 GHz H 2 O and 43 GHz SiO masers. Until our work, hydroxyl (OH) masers had not been detected either: Desmurs et al (2010) reported no detection of the 6 GHz OH excited lines, while Silverglate et al (1979) reported no detection of the 1612, 1665 or 1667 MHz OH lines. The absence of masers from oxygen-species is not surprising because of the carbon-rich nature of CRL 618.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Regarding the maser environment, Yoon et al (2014) reported no detection of 22 GHz H 2 O and 43 GHz SiO masers. Until our work, hydroxyl (OH) masers had not been detected either: Desmurs et al (2010) reported no detection of the 6 GHz OH excited lines, while Silverglate et al (1979) reported no detection of the 1612, 1665 or 1667 MHz OH lines. The absence of masers from oxygen-species is not surprising because of the carbon-rich nature of CRL 618.…”
Section: Introductionmentioning
confidence: 72%
“…They found 1720 MHz masers to have very similar velocity and location to the H 2 O masers. An excited OH maser of the 6035 MHz transition has also been detected toward K3-35, and, as for the 1720 MHz OH masers, the excited OH maser in K3-35 is coincident in position and velocity with H 2 O masers and may originate from the inner circumstellar envelope (Gómez et al 2009, Desmurs et al 2010. According to the model by Herpin & Cernicharo (2000), the region where OH and H 2 O are located in CRL 618 is within 1,400 a.u.…”
Section: Scenarios For the Origin Of The 4765 Mhz Oh Maser In Crl 618mentioning
confidence: 86%
“…Seaquist & Davis (1983) detected radio continuum (at 2, 6, and 20 cm) and OH (1612 MHz) maser emission with the VLA toward this source. Moreover, OH maser emission at 6035 MHz was detected toward this source with single-dish observations (Jewell et al 1985;Desmurs et al 2002Desmurs et al , 2010. However, References.…”
Section: Iras 19219+0947 (Vy 2−2)mentioning
confidence: 79%
“…They all show maser emission with strong asymmetry, i.e., preferentially blueshifted emission with respect to the stellar velocity (Uscanga et al 2012). One of them, K 3−35, shows OH maser emission at all four ground-state transitions (1612, 1665, 1667, 1720 MHz; Gómez et al 2009), as well as excited-state masers at 6035 MHz (Desmurs et al 2010). It is so far the only PN known to exhibit OH maser lines at 1720 MHz.…”
Section: Introductionmentioning
confidence: 99%